The city dimension of the productivity growth puzzle: the relative role of structural change and within-sector slowdown. (23rd March 2018) - Martin, Ron; Sunley, Peter; Gardiner, Ben; Evenhuis, Emil; Tyler, Peter
Abstract: Across OECD countries productivity growth has slowed, not just in recent years but over the past four decades: the so-called productivity puzzle. This paper examines the differing productivity growth paths of some 85 British cities since the beginning of the 1970s, and explores how far these paths reflect differences across cities in the pace and nature of structural change. We find that while northern cities led productivity growth over 1971–91 southern cities then led after 1991. However, at the same time, the rate of productivity growth slowed across almost all cities between these two periods. We find evidence of considerable structural convergence across cities and a general tendency for the degree of specialisation to fall. This then leads to a decomposition analysis which identifies the relative contribution of between-sector (structural change) and within-sector effects to city productivity growth. The analysis reveals that structural change – and especially the shift from manufacturing to services – has had a negative impact on productivity growth across all cities, but that within-sector productivity developments while positive and outweighing structural change effects, have also declined over the past 45 years, as well as varying across cities. These findings point to the need for further research on the causes of this slowdown in 'within-sector 'productivity growth and why those causes appear to differ from city to city. They also point to the need for a 'place-based' dimension to policies aimed at improving national productivity performance.